A strip line technique based 1 Gb/s, 70-dB linear dynamic range transimpedance amplifier towards LiDAR unmanned vehicle application. (August 2022) - Gorre, Pradeep; Vignesh, R.; Kumar, Sandeep
Abstract: 1This work reports a Microstrip Line (MSL) based Dual-Gate MOSFET (DGMOSFET) Transimpedance amplifier (TIA) for LIDAR unmanned vehicle application under different weather conditions. TIA (Design-I) is proposed under normal weather, while TIA (Design-II) for foggy weather conditions. TIA (Design-I) employs a variable gain common gate topology with post-amplification, resulting in high gain, wide bandwidth, and high dynamic range (DR). TIA (Design-II) incorporates a series MSL section at the input of TIA (Design-I), which further enhances the bandwidth performance. TIA (Design-I) realizes a fractional bandwidth of 104.3% with a transimpedance gain of 100.4 dBΩ and low input-referred noise (IRN) density of 4.29 pA/√Hz. TIA (Design-II) achieves a fractional bandwidth of 178.4% with transimpedance gain, IRN, and DR of 100.42 dBΩ, 3.81 pA/√Hz, and 70 dB, respectively. TIA (Design-II) demonstrates a 1 Gb/s data rate with a bit-error-rate < 10 −10 . The TIA (Design-I) and TIA (Design-II) consume the power of 33 mW and 39 mW under the supply voltage of 2 V.